Penggunaan Teknologi GIS untuk Identifikasi dan Pemetaan Daerah Rawan Banjir di Kota Malang - Yulaichah, Yulaichah; Kurniawan, Andri; Hizbaron, Dyah Rahmawati (Universitas Pendidikan Ganesha, 2025)
Indonesia is located between four major tectonic plates, making it vulnerable to various natural disasters, including floods caused by high rainfall, river sedimentation, and land-use changes. Malang City, as a growing urban area, has experienced an increasing frequency of floods over the past five years. This study aims to evaluate the factors contributing to flood vulnerability and produce a risk zoning map using Geographic Information System (GIS) technology. A quantitative approach was employed by analyzing parameters such as rainfall, soil type, slope gradient, elevation, land use, and river proximity using the weighted overlay method. The results indicate that high-risk areas include the districts of Klojen, Blimbing, Sukun, and Lowokwaru. Key factors include high rainfall intensity, limited infiltration areas, and proximity to major rivers. This zoning map is expected to assist the government in disaster mitigation planning, improving drainage infrastructure, and enhancing community resilience to floods.